2023
DOI: 10.3390/plants12142746
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Light Quality in Regulating Early Seedling Development

Abstract: It is well−established that plants are sessile and photoautotrophic organisms that rely on light throughout their entire life cycle. Light quality (spectral composition) is especially important as it provides energy for photosynthesis and influences signaling pathways that regulate plant development in the complex process of photomorphogenesis. During previous years, significant progress has been made in light quality’s physiological and biochemical effects on crops. However, understanding how light quality mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…A similar trend was also observed in lettuce seedlings grown under different daily light integrals [ 41 ]. The light spectrum is a critical signal that influences plant growth, development, and metabolic processes [ 42 ]. In this study, the leaf length of lettuce under the W+FR treatment was not significantly different from that under the W treatment, but the leaf length under the W+UV treatment was significantly shorter than that under the W treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend was also observed in lettuce seedlings grown under different daily light integrals [ 41 ]. The light spectrum is a critical signal that influences plant growth, development, and metabolic processes [ 42 ]. In this study, the leaf length of lettuce under the W+FR treatment was not significantly different from that under the W treatment, but the leaf length under the W+UV treatment was significantly shorter than that under the W treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygenic photosynthesis is the process through which solar energy is converted into chemical energy and used to reduce carbon dioxide (CO 2 ) into organic compounds. The produced carbohydrates are then exported to satisfy the metabolic needs of the non-photosynthetic cells of the plant, thus ensuring plant growth and development [ 22 , 23 ].…”
Section: Basics Of Plant Photosynthesis and Transpirationmentioning
confidence: 99%
“…Phoebe bournei have encounter many challenges to the environment which imposed by human activities but also natural environment (Li et al 2017), although establishment of most advanced and good seedling with agronomic characteristics but the survival and resistivity of of phoebia bournei remain challenge, under environmental factors like high temperature,salinity and drought (Da 2001). Different studies have shown that the phioebia bournei are more sensitive to biotic stress (Li et al 2022;Wei et al 2023). To ensure the survival and development of the Phoebea bournei population, studying the biochemical and molecular response of Phoebea bournei bZIP under different abiotic stress is very important.…”
Section: Introductionmentioning
confidence: 99%